The Society of St. Pius X: On the Road from the Roman Catholic Church, Through Schism, Towards Reconciliation with the Church... - Noworol OV, Anna (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
The article describes the history and polemics with the Church of the Priestly Brotherhood of St. Pius X. On the one hand, the article answers questions posed to the Church, in which the Brotherhood accuses the Church of errors where there are none. And it justifies that the Second Vatican Council did not make mistakes, only some people misinterpret it. On the other hand, the article, being written from the Roman Catholic side, indicates that the Brotherhood presents many values that are in line with the teachings of the Roman Catholic Church, and worth rediscovering; if members of the Brotherhood returned to full unity with the Roman Catholic Church, they could support the modern Church, as traditionalism can be a support against the threats of liberalism, feminism, syncretism and anticlericalism.